The Formation of Marketing Strategy of the Higher Educational Institutions to Increase their Efficiency - Cherkunova, N. G. (International Journal of Economics and Financial Issues, 2016)
The article deals with the problems connected with the marketing strategy formation under the higher educational institutions functioning. There are considered the main preconditions to implement the full-scale marketing investigation into the educational institutions in the system of the higher professional education. The necessity to use the market analytics, based on the marketing studies of not only private, but also state educational institutions, is proved. In the course of study, using the analysis of historical data, the dynamics of number of educational institutions was studied, as well as the factors, that influence on its structure. The system of stages was formed; it provides the educational institution with an opportunity to form the optimal marketing strategy. The notions of operational efficiency of the institution and marketing strategy are shown interconnected. The possibility to increase the institution efficiency, by means of creation of strict marketing strategy, is analyzed. Keywords: education, marketing, marketing strategy, the efficiency of the higher educational institution. JEL Classifications: M30, M38, I21, I25, I28